The eye and diabetes - Wong, Tien (Henry Stewart Talks, 2013)
Complications from diabetes, Diabetic retinopathy, Classification of diabetic retinopathy, Classification of diabetic macular edema, Clinical assessment of diabetic retinopathy, Optical coherence tomography, Epidemiology of diabetic retinopathy, Strategies of diabetic retinopathy management, Glucose control remains critical – Blood pressure just as important as glucose, Role of lipids, Multi-factoral interventions, Ocular treatment strategies of diabetic retinopathy, Novel therapy: Intraocular steroids, Anti-VEGF agents, Screening and awareness